The education facing the sexual difference/diversity - Rogério Diniz Junqueira (Universidade Estadual Paulista Júlio de Mesquita Filho, 2013)
The article advocates the destabilization of logic, assumptions, norms, values and practices that make it a normalizing space where and bodies, subjects and identities are built in accordance with heteronormative. Heterosexism and homophobia are not just problems that the school inherits from society, but the core elements of everyday life and the school curriculum: the school allows, cultivates and teaches heterosexism and homophobia. Struggles against homophobia based on essentialist assumptions or that do not question the heteronormative assumptions that generate and feed it are fairly limited. Difference, diversity and the encounter with the "other" have a great pedagogical importance. It demands the acknowledgment of sexual difference and diversity based on more open pedagogies, guided by democratic ethics and human rights.